Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1108/jeee-10-2018-0103
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and SME performance: the moderating role of emotional intelligence

Abstract: Purpose Lack of extant studies on the moderating role of emotional intelligence on the relationship between social capital and firm performance necessitated this study. The purpose of this paper is to examine the extent to which emotional intelligence moderates the relationship between social capital and small and medium-scaled enterprises’ (SMEs’) performance. Design/methodology/approach A total of 1,532 SMEs were selected through simple random sampling technique from a population of 5,009 SMEs. Structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 62 publications
4
26
0
3
Order By: Relevance
“…Second, this study developed a new integrated measurement of SC. This scale has seven facets with a total of twenty-eight indicators, which was confirmed to be more adequate and rigorous than scales developed by past studies, such as the measure of SC proposed or adopted by Boohene et al (2019), Chmel ıkov a et al (2019), and Sallah and Caesar (2020). It is also more suitable, reliable and rigorous than the SC statements proposed by Gomez-Limon et al (2014).…”
Section: Effect Of Social Capital On Agribusinessmentioning
confidence: 59%
See 1 more Smart Citation
“…Second, this study developed a new integrated measurement of SC. This scale has seven facets with a total of twenty-eight indicators, which was confirmed to be more adequate and rigorous than scales developed by past studies, such as the measure of SC proposed or adopted by Boohene et al (2019), Chmel ıkov a et al (2019), and Sallah and Caesar (2020). It is also more suitable, reliable and rigorous than the SC statements proposed by Gomez-Limon et al (2014).…”
Section: Effect Of Social Capital On Agribusinessmentioning
confidence: 59%
“…In fact, as the implication of Morrow et al (2017), its existing measurement is in a vague methodology or a lack of theory-based and validated measurements (Snoxell et al, 2006). As a consequence, most of the existing empirical studies apply partial approaches with one or a few facets of SC (Seghers et al, 2012;Morrow et al, 2017;Xu et al, 2018;Boohene et al, 2019;Chmel ıkov a et al, 2019;Calcagnini and Perugini, 2019;Cofr e-Bravo et al, 2019;Sallah and Caesar, 2020), while it is a multidimensional construct (Nahapiet and Ghoshal, 2000;Gedajlovic et al, 2013). Thus, scholars need to weigh each measure depending on the context of the study before applying for their studies (Veerle et al, 2012).…”
Section: Effect Of Social Capital On Agribusinessmentioning
confidence: 99%
“…Xu & Li (2019) even added that intellectual capital is positively associated with firm earnings, operation efficiency, and profitability. Along with that finding, social capital and financial capital also have shown that it has positive and significant influences on business (financial) performances among SMEs around the word (Abbas, 2018;Adlešič & Slavec, 2012;Boohene et al, 2019;Chittithaworn et al, 2011;Fatoki, 2011;Philip, 2011;Omar & Azmi, 2020;Sombolayuk et al, 2019;Utari & Dewi, 2014). Nakku et al (2020) added that the effect of financial capital on SME's performance will be stronger when government support existed.…”
Section: Introductionmentioning
confidence: 74%
“…Due to the entrepreneur's immersion in their jobs and a blurred line between work and social life, an entrepreneur's social life quality is compromised. Their desire to be part of a social network is essential to relieving entrepreneurial jobs' pressure [106]. Further, as their work and social lives become intertwined, the quality of social life suffers compared to the entrepreneurs' perceived social life.…”
Section: Discussionmentioning
confidence: 99%